A comparative study of single and double incision for L4/5 and L5/S1 double-level percutaneous interlaminar lumbar discectomy - Tang, Yingchuang; Liu, Zixiang; Liu, Hao; Zhang, Junxin; Zhu, Xiaoyu; Qian, Zhonglai; Yang, Huilin; Mao, Haiqing; Zhang, Kai; Chen, Hao; Chen, Kangwu (Frontiers in Surgery, 2022)
Objective: To investigate the clinical outcome of single- and double-incision for double-level percutaneous interlaminar lumbar discectomy. Methods: A retrospective analysis was performed involving patients with L4/5 and L5/S1 double-level lumbar disc herniation who received percutaneous interlaminar lumbar discectomy (PEID) in our hospital from January 2017 to December 2020. These enrolled patients were divided into single- and double-incision groups with 25 patients in each group. We compared the incision length, operation time, fluoroscopy times and length of hospital stay between the two groups. Meanwhile, postoperative visual analogue scale (VAS), Oswestry Disability Index (ODI), Japanese Orthopedic Association score (JOA) and modified MacNab standard were used to evaluate the outcomes of the patients within the two groups. Results: It showed that the single-incision group performed better than double-incision group in incision length, operation time and fluoroscopy times (P<0.001). The VAS score, JOA score and ODI index in the two groups were significantly decreased at the time points of post-surgery, 1 month after surgery and the last follow-up (P<0.01), but there was no statistical significance between the two groups involving above parameters(P>0.05). At the last follow-up, the excellent and good rates of MacNab efficacy in the two groups were 92% and 88% respectively, but no significant difference was observed between the two groups (P>0.05). Conclusion: Both the single- and double-incision approaches are effective and safe for the management of L4/5 and L5/S1 double-level LDH. The single-incision PEID for the treatment of L4/5 and L5/S1 double-segment lumbar disc herniation has advantages of less trauma, fewer intra-operative fluoroscopy times, shorter operation time，as compared to the double-incision. However, the operation of double-segment LDH through single laminar incision is difficult, the learning curve is steep and the professional skill is highly required. Importantly, the surgical indications should be strictly grasped.